Supervisi Kepala Sekolah Pengaruhnya terhadap Kinerja Guru Sekolah Dasar - Januar Barkah; Fahmi Hidayat; Nurbaity Nurbaity (INTELEKTIUM, 2021)
The aims of this study were to determine the effect of principal's supervision on teacher performance. This type of research is a quantitative descriptive research. The population in this study were 43 people from the Integrated Islamic Elementary School, South Jakarta. Samples were taken as much as 30% of the total population, the number of samples in this study amounted to 43 respondents. The instrument used is a questionnaire. This study concludes that: There is an effect of supervision on teacher performance. Based on the tcount value for Supervision (X) of 6,937 while the ttable value for n = 43 is 2,048. So 6,937 > 2,048 or rcount > ttable, because the hypothesis is formulated, if the value of tcount > ttable, then H0 is rejected and Ha is accepted. Meanwhile, based on the correlations table, R of 0,735 was obtained using the formula KD = R2 x 100%, the result was 54,02%.